2021
DOI: 10.3390/su13147653
|View full text |Cite
|
Sign up to set email alerts
|

Smart Evaluation of Green Campus Sustainability Considering Energy Utilization

Abstract: With the change in energy utilization, a fast and accurate evaluation method is of great importance to promote green campus sustainability. In order to improve the feasibility and timeliness of evaluation, an intelligent evaluation model based on dynamic Bayesian inference and adaptive network fuzzy inference system (DBN-ANFIS) is proposed. Firstly, from the perspective of sustainability and considering the changes in energy utilization, a green campus evaluation index system is constructed from four levels: c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The analysis should encompass the identification of trends and patterns in the results, including the community's preferences and priorities with respect to sustainability and energy efficiency [71,72]. It is imperative to determine whether the implemented measures are consistent with the community's expectations and requirements, and to identify areas where further work is necessary to satisfy the community's needs [73,74]. The assessment of user willingness through a survey is an effective methodology for ensuring the sustainability of university campuses and actively involving the university community in energy saving and efficiency initiatives [75,76].…”
Section: A Brief Literature Reviewmentioning
confidence: 99%
“…The analysis should encompass the identification of trends and patterns in the results, including the community's preferences and priorities with respect to sustainability and energy efficiency [71,72]. It is imperative to determine whether the implemented measures are consistent with the community's expectations and requirements, and to identify areas where further work is necessary to satisfy the community's needs [73,74]. The assessment of user willingness through a survey is an effective methodology for ensuring the sustainability of university campuses and actively involving the university community in energy saving and efficiency initiatives [75,76].…”
Section: A Brief Literature Reviewmentioning
confidence: 99%
“…It can be observed that the per capita plastic usage and waste of students at Xi'an Shiyou University are at a low level. In recent years, both domestic and international universities have actively i mented measures to establish universities as pivotal platforms for reducing plastic sumption in society [36][37][38][39]. The primary objective of Chinese colleges and universi to impart knowledge on ecological civilization to students, guiding them towards a In recent years, both domestic and international universities have actively implemented measures to establish universities as pivotal platforms for reducing plastic consumption in society [36][37][38][39].…”
Section: Analysis Of Campus Plastic Materials Flow Characteristicsmentioning
confidence: 99%
“…In recent years, both domestic and international universities have actively i mented measures to establish universities as pivotal platforms for reducing plastic sumption in society [36][37][38][39]. The primary objective of Chinese colleges and universi to impart knowledge on ecological civilization to students, guiding them towards a In recent years, both domestic and international universities have actively implemented measures to establish universities as pivotal platforms for reducing plastic consumption in society [36][37][38][39]. The primary objective of Chinese colleges and universities is to impart knowledge on ecological civilization to students, guiding them towards adopting ecological consumption practices and implementing waste classification measures to minimize plastic usage.…”
Section: Analysis Of Campus Plastic Materials Flow Characteristicsmentioning
confidence: 99%
“…Several studies have recommended evaluation standards for low-carbon campuses based on the perspective of campus construction and have implemented various models to construct evaluation systems based on different dimensions. For instance, Zhao et al [36] proposed a green campus evaluation indicator system founded on dynamic Bayesian inference and adaptive network fuzzy inference system (DBN-ANFIS). Na et al [37] formulated an expert questionnaire, compared the Analytic Hierarchy Process (AHP) with the Entropy Weight Method (EWM), and assigned different weights to four aspects: management mechanism, low-carbon culture, renewable energy utilization, and emission reduction measures.…”
Section: Low-carbon Campus Evaluation Indicators and Willingness Towa...mentioning
confidence: 99%